Development of Village-Owned Enterprises (BUMDes) for Prosperity through Community Services (Case Study in Damarwulan Village, Kepung District, Kediri Regency) - Merinda Armi; Nurmahmudah Nurmahmudah (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research examines the impact of Village-Owned Enterprises (BUMDes) on Damarwulan Village's economic development. It explores BUMDes' significance as a village-owned legal entity managed independently with capital from local resources. Method: We employ descriptive qualitative methods, gathering data from various sources, including manuscripts, interviews, and official documents. The study focuses on BUMDes' existence, economic contributions, and factors influencing their success. An analysis follows an Interactive Model involving data reduction, presentation, and conclusions. Practical Applications: Our findings have practical implications for rural development and local governance. They inform policymakers and communities about the potential benefits and challenges of BUMDes, aiding decisions on supporting and establishing such enterprises. Conclusion: BUMDes significantly enhance Damarwulan Village's economy, offering valuable insights for rural development and governance practices, ultimately improving socio-economic conditions.